Molecular survey of knockdown resistance to pyrethroids in human scabies mites. (30th August 2013) - Andriantsoanirina, V.; Izri, A.; Botterel, F.; Foulet, F.; Chosidow, O.; Durand, R.; Bottieau, E.
Abstract There are growing concerns about the emergence of resistance of Sarcoptes scabiei to permethrin and other pyrethroid derivatives. Sarcoptes scabiei mites collected from 40 patients visiting two hospitals near Paris, France, were genotypically characterized considering two parts of their voltage‐sensitive sodium channel gene. No nucleotide polymorphism resulting in a codon change at codon 733 or other positions associated with knockdown resistance in other arthropods has been identified. These data may establish a reference line for future surveys of the susceptibility of S. scabiei in the area.